Hydrological, biogeochemical and carbonate system data in coastal waters and in glacier drainage systems in Kongsfjorden (Svalbard), during July-August 2016 - Cantoni, Carolina; Hopwood, Mark James; Clarke, Jennifer; Chiggiato, Jacopo; Achterberg, Eric Pieter; Cozzi, Stefano (Supplement to: Cantoni, Carolina; Clarke, Jennifer; Chiggiato, Jacopo; Achterberg, Eric Pieter; Cozzi, Stefano (2020): Glacial drivers of marine biogeochemistry indicate a future shift to more corrosive conditions in an Arctic fjord. Journal of Geophysical Research: Biogeosciences, https://doi.org/10.1029/2020JG005633, 2019)
A detailed survey of a high Arctic fjord (Kongsfjorden, Svalbard), subjected to a large glacier discharge, was carried out from 24 July to 13 August 2016. Field activities addressed the identification of the effects of glacier and iceberg melting on the evolution of nutrient, dissolved organic matter and carbonate systems in this coastal marine environment. Hydrological (CTD downcasts) and biogeochemical (bottle sampling) data were collected during six oceanographic surveys in the inner area of the fjord, in concomitance to the annual phase of maximum air warming. An extensive sampling was also carried out in all glacier drainage systems located around the fjord and from several iceberg samples, in order to characterize all freshwater loads. The dataset includes hydrological data (T, Sal., density) carbonate chemistry data (pH, DIC, TA) and the concentrations of dissolved oxygen (DO), inorganic nutrients (NO3-, NO2-, NH4+, PO43-, SiO2), dissolved organic matter (DOC, DON) and some micronutrients (Fe, Mn).
Keywords: Carbonate chemistry; glacier; Iceberg; nutrients; Ocean acidification; runoff